Building Research-Practice Partnerships as a District-Led Initiative: A High-Leverage Strategy for System Improvement - Muñoz, Marco A (Planning & changing, 2016)
Research-Practice Partnerships (RPP) can enable and support an evidence-based school culture for decision-making in districts across the nation. Based on our experiences in a large urban district, a key element for a successful RPP is to understand that school districts have their own research needs/agenda typically articulated in strategic plans. In addition of having a good "fit" in terms of the research agenda, the RPP needs to be guided by clear guiding principles such as research utility, practicality, technical accuracy, and ethical soundness in the context of a well-designed data access and human subject's research protection framework. School districts can be great research partners as long as there is a clear focus on improving student learning and producing useful, timely, accurate, valid, reliable, and actionable research.